Enhanced detection sensitivity of neuronal activity patterns using CaMPARI1 vs. CaMPARI2 - Das, Aniruddha; Margevicius, Daniel; Borovicka, Julie; Icardi, Jacob; Patel, Davina; Paquet, Marie-Eve; Dana, Hod (Frontiers in Neuroscience, 2023)
Calcium-modulated photoactivatable ratiometric integrator (CaMPARI) is a calcium ion (Ca2+)- and light-dependent genetically-encoded fluorescent activity integrator that can capture snapshots of neuronal activity through an irreversible process known as photoconversion. This unique property was previously used to label neurons based upon their tuning properties in order to map synaptic connectivity and to record large-scale neuronal activity in freely-moving mice without attaching any mechanical device to them. The latest version of CaMPARI (CaMPARI2) was engineered to enhance the contrast generated by photoconverting the green protein to the activity-dependent red form and to reduce the Ca2+-independent photoconversion rate compared to the first generation of CaMPARI (CaMPARI1). However, here we show that this optimization process also resulted in reduced sensitivity of labeling active neurons in the mouse cortex and hippocampus. Through side-by-side comparison of the two CaMPARI sensors under several experimental conditions, we show that CaMPARI1 exhibits a substantially higher red-to-green ratio in active cells than CaMPARI2. In addition, we show that CaMPARI1 also functions as a more sensitive traditional Ca2+ sensor than CaMPARI2 by producing larger activity-driven dynamic fluorescence changes in the tested neurons. Therefore, we conclude that during the optimization process of CaMPARI2, some of the sensor’s characteristics were not predicted properly by in vitro screening assays and suggest including additional in vivo screening steps to increase the predictability of screening pipelines.